EKSISTENSI PALINGGIH DEWA HYANG CIK DI MERAJAN ARYA GAJAH PARA DESA BANYUATIS KECAMATAN BANJAR KABUPATEN BULELENG (PERSPEKTIF SOSIORELIGIUS) - Ketut Agus Nova (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Palinggih God of the Lord Cik worships God or figure from the Chinese state so that its palinggih form is characterized in red and wear the equipment such as Konhucu or Buddhist religious shrine. The results of this study are: (1) The form of (a) the catastrophic murders of the Chinese by the Arya Gajah Para family were then conceived and on the advice of families who took the wife of China to build the Palinggih god of the Lord Cik, (b) the complex of Arya Gajah Para (c) Palinggih God Almighty in it there are several parts that is the existence of palinggih god goddess of Syahbanadar god and God of Miss Cik (d) the way of worship using banten but there are special tools such as religious ritual konhucu. (e) The means used are all red in color such as paints, mugs, decorations, incense and so on red. (2) Functions consist of (a) increasingntrust and confidence in God, (b) heritage legacy will remain awake. (c) social life with fellow Arya Gajah Para family members remain in the family. (d) a combination of two cultures, namely Chinese and Balinese culture. (3) The value of socioreligius education consists of (a) social education that is family given learning about the importance of social life (b) religious educationis given learning that is very important belief and belief (c) behave (d) aesthetics / beauty education that is the media in awareness of the importance of the importance of the society in raising the faith and hostility of devotion. (e) this life will not be peaceful without tolerance with one another or outside the tribe and religion. (f) Palinggih Dewa Hyang Cik people are taught to always maintain, improve harmony between family, tribal and religion